Clinical variants of skin and mucous membrane lesions in systemic lupus erythematosus with juvenile onset - M. I. Kaleda; S. O. Salugina; I. P. Nikishina; A. N. Arefieva (Современная ревматология, 2023)
Skin and mucous membrane lesions are frequently seen in systemic lupus erythematosus (SLE) with the juvenile onset (juSLE), and they are extremely diverse. Skin manifestations can be the initial sign of the disease, they often respond first to adequate therapy, and recurrence or the appearance of a new type of lesions is the earliest indicator of exacerbation in many patients. In severe cases, skin lesions can lead to irreversible cosmetic defects, significantly affecting the quality of life. The article presents the clinical manifestations of various variants of skin and mucous membrane lesions in SLE with a debut in childhood and adolescence, their recognition is important for the timely diagnosis of SLE, as well as the correction of therapy for an existing disease, which improves the long-term prognosis and quality of life of patients.